Sentinel Node Biopsy for Endometrial Cancer by Retroperitoneal Transvaginal Natural Orifice Transluminal Endoscopic Surgery: A Preliminary Study - Huber, Daniela; Hurni, Yannick (Frontiers in Surgery, 2022)
Objective: The primary objective was to determine the intraoperative and postoperative surgical complications of sentinel lymph node biopsy (SLNB) by retroperitoneal transvaginal natural orifice transluminal endoscopic surgery (vNOTES). The secondary objective was to assess the feasibility of this surgical technique. Methods: This was a descriptive study realized in a non-university hospital in Switzerland. Seven patients with endometrial cancer or endometrial complex atypical hyperplasia underwent surgical staging with SLNB by retroperitoneal vNOTES using an indocyanine green-based near-infrared fluorescence imaging technique (October 2021-February 2022). Results: The median operative time was 113 (81-211) minutes. The median estimated blood loss was 20 (20-400) mL. The overall bilateral detection rate was 100% (7/7). Upon histopathological examination, 5 patients presented an endometrial adenocarcinoma, and we found endometrial complex atypical hyperplasia in 2 cases. We successfully completed all procedures without significant intraoperative complications, but 1 case required conversion to conventional laparoscopy. The median postoperative stay was 2 (2-4) days, and we observed no postoperative complications during this period. We observed 1 case of postoperative deep vein thrombosis and an asymptomatic vaginal vault hematoma in the same patient. Conclusions: Our preliminary study suggests that retroperitoneal vNOTES could be a feasible, safe, and valuable approach to perform SLNB in endometrial cancer. However, strong evidence of its feasibility, the effective benefits, and the long-term oncological outcomes is needed before expanding the use of vNOTES in endometrial cancer outside study settings.